Influence of buffered propionic and fumaric acids on starter pig performance - J R Bergstrom; T L Signer; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1994)
A 28 d growth trial was conducted to determine the effects of adding organic acids to a Phase I starter diet on pig performance. At weaning (13 ± 2 d of age and 8.86 lb), 300 pigs were blocked by weight and allotted to each of five diets. The control diet was corn-soybean meal based; contained 20% dried whey, 7.5% spray-dried porcine plasma, and 1.75% spray-dried blood meal; and was formulated to 1.5% lysine, .9% Ca, and .8% P. Luprosil NC (.4%; a buffered liquid propionic acid), Luprosil salt (.4%; a buffered dry propionic acid), fumaric acid (1.5%), and a combination of Luprosil NC (.4%) and fumaric acid (1.5%) replaced corn in the control diet to provide the four additional experimental treatments. Pigs fed diets containing any of the acid sources had improved average daily gain (ADG) and feed efficiency (F/G) during Phase I (d 0 to 14 postweaning) compared with those fed the control diet. No differences occurred in ADG among pigs fed any of the acid sources; however, pigs fed the diet containing fumaric acid had improved F/G when compared to those fed Luprosil salt during Phase 1. No differences occurred in growth performance when pigs were fed a common diet during Phase II (d 14 to 28 postweaning), but ADG and F/G were improved during the overall 28 d trial when the pigs were fed acidified diets during Phase 1. These results suggest that adding organic acids (buffered propionic or fumaric acid) to a diet containing 20% dried whey and 7.5% porcine plasma enhances growth performance from d 0 to 14 postweaning.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter; Acid; Diet; Performance